The Campylobacter jejuni flagellar V-ring discerns viscosity levels to alter swimming velocity, metabolic gene expression, and fitness - Deborah A. Ribardo; Nanki K. Singh; Morgan Beeby; David R. Hendrixson (Proceedings of the National Academy of Sciences, 2026)
Campylobacter jejuni is an intestinal commensal of birds and animals and a leading cause of bacterial diarrheal disease in humans. In hosts, C. jejuni primarily resides in the mucus layer atop the lower intestinal epithelium. Persistence in this niche requires a single flagellar motor at both C. jejuni poles that generates high torque for flagellar rotation to facilitate motility and high swimming velocities. Unlike many bacterial flagellates, C. jejuni swimming velocity increases as external viscosity increases. We identified a complex formed by FlgV, VidA, and VidC (Cjj81176_1732) positioned near the MS-ring-rotor junction in the flagellar motor we annotated as the V-ring. Viscosity-influenced growth, modulation of swimming velocity, and transcription of iron/heme acquisition, respiratory, and energy-generating systems were dependent on the V-ring. C. jejuni Δ flgV and Δ vidC populations lacking a complete V-ring were motile, but could not optimally modulate swimming velocity. Like nonmotile flagellar stator or filament mutants, motile V-ring mutants had in vivo and in vitro growth and viability defects and dysregulated transcription of genes likely impacting physiology. Because the V-ring mutants behaved similarly as nonmotile mutants that experience little to no viscous drag on the filament, we propose C. jejuni V-ring mutants cannot detect viscous drag on their rotating filaments. We propose the V-ring evolved in C. jejuni and potentially other bacteria producing high torque flagellar motors to monitor external viscosity information via viscous drag on the rotating flagellar filament to adjust swimming velocity, transcription, and physiology for optimal fitness in different host lower intestinal niches.